Promise or precarity? South African attitudes towards the automation revolution. Issue 4 (4th July 2022) - Roberts, Benjamin J.; Gordon, Steven L.; Struwig, Jarè; Bohler-Muller, Narnia; Gastrow, Michael
ABSTRACT: Rapid technological advancement has prompted growing debate about the promise and challenges of the Fourth Industrial Revolution (4IR) for societies. Some believe it will improve efficiency, productivity and quality of life, while others emphasise the risk of job loss, inequality and social exclusion. Despite the salience of these changes for human development, public opinion research on these issues remains limited in South Africa. Using data from the South African Social Attitudes Survey (SASAS), we examine the extent and determinants of the public's acceptance of robots and automation. The findings suggest that aversion to such technological change remains fairly high, and is informed by age, class, perceived labour market vulnerability, scientific knowledge, and confidence in government to manage adverse human consequences. The article concludes by arguing that national 4IR policy framework needs to consider the reservations expressed by many South Africans, and develop measures to protect the dignity and well-being of citizens across the life course.